Greening-up effects on streamflow and evapotranspiration in Mediterranean catchments. An example of Taibilla catchment (SE Spain) - Pérez Cutillas, Pedro; Cataldo, Maria Francesca; Zema, Demetrio Antonio; de Vente, Joris; Boix-Fayos, Carolina (BOSQUE, 2018)
Important land cover changes were documented in several areas of the Mediterranean basin with associated hydrological effects. This paper aims at contributing to the characterization of land use changes and vegetation cover in a basin representative of the Mediterranean mountain range, and quantifying the impact of those changes on lateral and vertical flows (discharge and evapotranspiration, respectively). For this purpose, a series of precipitation data and some components of the hydrological cycle were analyzed: streamflow-runoff in two periods (1933-1948 and 1996-2012). In addition, a spatial analysis of land use changes was carried out; this information was used for the spatial analysis of the curve number and evapotranspiration. Main results indicated that precipitation had not changed significantly between both periods, while streamflow declined by a 43 %, together with the loss of 63 % of agricultural areas that were replaced by shrubland and forest. Evapotranspiration increased in 57 % of the drainage area, with an average increase of 20 mm year-1. In general, the partition of rainfall was readjusted due to the recovery and changes of the natural vegetation cover, facilitating a redistribution of water within the hydrological cycle. As a result, the observed increase of vertical fluxes and the decrease of horizontal ones could potentially affect the hydrological resources of the area.